Obstacles to the creation of gas trading hubs and a price index in Northeast Asia. Issue 2 (4th March 2019) - Kim, Younkyoo
Abstract: On the face of it, Asian gas hub pricing dynamics in 2014–2017 look similar to that of Europe in 2009–2012. The central argument of this article is that the path to an Asian liquefied natural gas (LNG) hub seems to be quite different than in Europe. Unique challenges to a posited gas hub pricing have not been fully illuminated. One of the hypotheses of this article is that Asia is by no means Europe, and Asia will have its own unique path to a gas hub pricing. Complexity and uncertainty around the global and Asian supply and demand balance increases significantly until the mid-2020s. A market consensus view has developed that the global LNG market will remain oversupplied for the rest of this decade and well into the 2020s. While this consensus is currently being supported by a range of buyers and producers, it is increasingly coming under challenge. For Asia, it makes more sense to anticipate a virtual LNG hub and not natural gas trading hub.